2019
DOI: 10.1002/jgm.3075
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNA expression in sentinel lymph nodes from patients with breast cancer via RNA sequencing for diagnostic accuracy

Abstract: Background Sentinel lymph node (SLN) property assessment (with or without metastasis) is important when deciding the surgery for breast cancer; however, the current diagnosis of SLN metastasis remains to be studied. microRNAs (miRNAs) have been confirmed previously as a molecular marker for the diagnosis, development and prognosis of tumors. However, the detailed role of miRNAs in the diagnosis of SLN metastasis has not been reported. Methods The present study aimed to explore the potential use of miRNAs in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…The latter does not come as a surprise as there is much evidence indicating the direct binding of MALAT1 to miR-1-3p, wherein MALAT1 could negatively regulate the expression of miR-1-3p in esophagus cancer cells [ 29 ]. In addition, the study carried out by Sun et al evidenced downregulation of miR-1-3p in BC patients with sentinel lymph node metastasis, which is in accordance with our findings [ 30 ]. High expression of miR-1-3p was further shown to confer an inhibitory effect on BC cell viability, invasion, and migration, while simultaneously suppressing tumor formation and metastasis [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…The latter does not come as a surprise as there is much evidence indicating the direct binding of MALAT1 to miR-1-3p, wherein MALAT1 could negatively regulate the expression of miR-1-3p in esophagus cancer cells [ 29 ]. In addition, the study carried out by Sun et al evidenced downregulation of miR-1-3p in BC patients with sentinel lymph node metastasis, which is in accordance with our findings [ 30 ]. High expression of miR-1-3p was further shown to confer an inhibitory effect on BC cell viability, invasion, and migration, while simultaneously suppressing tumor formation and metastasis [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…Taken together, the results of the present study suggested that miR-96 may be an oncogene associated with CCA tumor development. Previous studies have also indicated that miR-96 functions as an oncogene in various types of cancer, including breast and non-small cell lung cancer, as well as cervical carcinoma (30)(31)(32). For instance, the expression of miR-96 is upregulated in human cervical carcinoma cells and may promote the proliferation and tumorigenicity of cervical cells by silencing PTPN9 (32).…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Besides, it may play a tumor suppressor role by directly regulating ADAM9 and MMP7 in breast cancer. [ 20 ] However, the regulation mechanism of some miRNAs in the tumor has not been reported yet, so more researches need to be conducted in the future, especially in breast cancer.…”
Section: Discussionmentioning
confidence: 99%